A novel echocardiographic method for estimation of pulmonary artery wedge pressure and pulmonary vascular resistance. (10th February 2021) - Chubuchny, Vladislav; Pugliese, Nicola Riccardo; Taddei, Claudia; Poggianti, Elisa; Spini, Valentina; Barison, Andrea; Formichi, Bruno; Airò, Edoardo; Bauleo, Carolina; Prediletto, Renato; Pastormerlo, Luigi Emilio; Coceani, Michele; et al.
Abstract: Aims: This study aimed to evaluate a novel echocardiographic algorithm for quantitative estimation of pulmonary artery wedge pressure (PAWP) and pulmonary vascular resistance (PVR) in patients with heart failure and pulmonary hypertension (PH) scheduled to right heart catheterization (RHC). Methods and results: In this monocentric study, 795 consecutive patients (427 men; age 68.4 ± 12.1 years) undergoing echocardiography and RHC were evaluated. Multiple regression analysis was performed to identify echocardiographic predictors of PAWP and PVR measured by RHC in the derivation group (the first 200 patients). The diagnostic accuracy of the model was then tested in the validation group (the remaining 595 patients). PH was confirmed by RHC in 507 (63.8%) patients, with 192 (24.2%) cases of precapillary PH, 248 (31.2%) of postcapillary PH, and 67 (8.4%) of combined PH. At regression analysis, tricuspid regurgitation maximal velocity, mitral E/e′ ratio, left ventricular ejection fraction, right ventricular fractional area change, inferior vena cava diameter, and left atrial volume index were included in the model ( R = 0.8, P < 0.001). The model showed a high diagnostic accuracy in estimating elevated PAWP (area under the receiver operating characteristic curve = 0.97, 92% sensitivity, and 93% specificity, P < 0.001) and PVR (area under the receiver operating characteristic curve = 0.96, 89% sensitivity, and 92% specificity, P < 0.001), outperforming 2016 American Society of Echocardiography/European Association of Cardiovascular Imaging recommendations ( P < 0.001) and Abbas' equation ( P < 0.001). Bland–Altman analysis showed satisfactory limits of agreement between echocardiography and RHC for PAWP (bias 0.7, 95% confidence interval −7.3 to 8.7) and PVR (bias −0.1, 95% confidence interval −2.2 to 1.9 Wood units), without indeterminate cases. Conclusions: A novel quantitative echocardiographic approach for the estimation of PAWP and PVR has high diagnostic accuracy in patients with heart failure and PH.